2022
DOI: 10.2196/30457
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of eHealth and mHealth Interventions Supporting Children and Young People Living With Juvenile Idiopathic Arthritis: Systematic Review and Meta-analysis

Abstract: Background Juvenile idiopathic arthritis (JIA) management aims to promote remission through timely, individualized, well-coordinated interdisciplinary care using a range of pharmacological, physical, psychological, and educational interventions. However, achieving this goal is workforce-intensive. Harnessing the burgeoning eHealth and mobile health (mHealth) interventions could be a resource-efficient way of supplementing JIA management. Objective This … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 105 publications
(469 reference statements)
0
17
0
Order By: Relevance
“…Two articles [ 51 , 57 ] reported that electronic intervention was ineffective in relieving anxiety, and another [ 59 ] showed mixed views. Electronic intervention was reported to be ineffective for depression in 2 studies [ 51 , 60 ], whereas 3 articles [ 54 , 55 , 59 ] provided mixed conclusions. There were mixed results regarding the effect of pain relief, with some studies [ 50 , 51 ] indicating no effect on pain relief, and others [ 55 , 61 ] reporting the opposite.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two articles [ 51 , 57 ] reported that electronic intervention was ineffective in relieving anxiety, and another [ 59 ] showed mixed views. Electronic intervention was reported to be ineffective for depression in 2 studies [ 51 , 60 ], whereas 3 articles [ 54 , 55 , 59 ] provided mixed conclusions. There were mixed results regarding the effect of pain relief, with some studies [ 50 , 51 ] indicating no effect on pain relief, and others [ 55 , 61 ] reporting the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…Among the published systematic evaluations, studies on the application of electronic interventions included patients with cancer, respiratory diseases, and arthritis. In terms of quality of life, 3 studies [49][50][51] reported that electronic interventions were ineffective, but 7 [52][53][54][55][56][57][58] reported improvement in quality of life. Two articles [51,57] reported that electronic intervention was ineffective in relieving anxiety, and another [59] showed mixed views.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
See 3 more Smart Citations